Biodiversity in an agroecological landscape: Harnessing ecosystem services for agriculture - Krishnan, Abhiram; Sinu, Palatty Allesh; Baby, Ashly; Hariraveendra, M; Viswan, Gopika; Jose, Thomas; Krishnan, Smitha; Maliappan, Sudharsan; Acharya, Pradyumna; Pawar, Manohar (2025)
Modern agricultural practices have significantly harmed the environment, with biodiversity loss being a major consequence of intensified farming. Biodiversity in farmlands is essential for ecosystem services like pollination, which supports crop yield and quality. Approximately 35% of global crops rely on animal pollination to some degree, with cross-pollination further enhancing fruit size, flavor, and shelf life. Pollinator dependent crops are known to be nutritionally dense leading to a rising demand for such crops, thus highlighting the need for sustainable farmland management that preserves biodiversity and optimizes ecosystem services. In addition to intensive agricultural practices, deforestation for agriculture further degrades ecosystems, disrupting pollinator populations and natural pest control mechanisms. Agricultural landscapes with natural vegetation support beneficial insects, including pollinators and predators of agricultural pests. However, while pests contribute to yield loss, pesticide use threatens both pollinators and natural predators. Thus, farmland management strategies should balance productivity with arthropod diversity conservation. Biodiversity and biotic interactions in agro-ecosystems are shaped by local and landscape-level factors, including environmental conditions, management practices, and habitat diversity. Organic farming and diverse landscapes enhance biodiversity and promote key ecosystem services. This study examines how landscape variables influence insect biodiversity and interactions contributing to pollination and biocontrol, using homestead gardens as a model. With self-help groups and NGOs driving reforestation efforts, we assess the hypothesis that forest cover positively impacts insect diversity and ecosystem services in winter croplands of Mandla, Madhya Pradesh. The study found complimentary benefits from farmlands and forests in the form of ecosystem services that were crucial for crop production. In addition to forage resources crops additionally provided nesting resources for pollinators. Extent of forest and farm diversity were crucial in sustaining important ecosystem services such as pollination and biocontrol.